2001
DOI: 10.1300/j120v34n72_17
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Informal Professional Development into the Work of Reference

Abstract: The dynamic environment of reference work demands that reference staff engage in ongoing professional development opportunities. The Bio-Medical Library at the University of Minnesota offers an informal, flexible, and highly interactive professional development program for those who staff the Reference Desk. The program, suitable for librarians and paraprofessionals at all levels of experience, combines a variety of opportunities, among them e-sessions on new tools, a review of basic Reference Desk competencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…However, Smith, Kendall andHulin (1969, cited in Saba, 2011) stated that JS is multi-faceted variable, implies employees' satisfaction is linked with different facets of work. Operationally defining JS as a multifaceted term, research literature reported the dominant facets of JS as promotion, supervision, work environment and remunerations (Ivancevich & Matteson, 1980;Block & Kelly, 2001;Testa, 2001). Further, Luthans (1998) categorized these facets as; 1) intrinsic JS-related with the type of work that make the job, for example skills, etc.…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Smith, Kendall andHulin (1969, cited in Saba, 2011) stated that JS is multi-faceted variable, implies employees' satisfaction is linked with different facets of work. Operationally defining JS as a multifaceted term, research literature reported the dominant facets of JS as promotion, supervision, work environment and remunerations (Ivancevich & Matteson, 1980;Block & Kelly, 2001;Testa, 2001). Further, Luthans (1998) categorized these facets as; 1) intrinsic JS-related with the type of work that make the job, for example skills, etc.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…According to Pan and Hovde (2010), professional development programs are needed for librarians to obtain the needed competencies that are essential for effective performance. Similarly, Block and Kelly (2001) recommended in-service training to acquire the needed competencies that may further reduce work related anxiety, enhance workers' current levels of competencies and may escalate job satisfaction. According to Faraji, Badraghe and Masoumi (2013), training in the needed skills may enhance the performance of workers.…”
Section: The Relationship Of Tmc With Jsmentioning
confidence: 99%
“…if users continue to perceive academic librarians as knowledgeable and service-oriented, the library will remain central to a university's mission and goals" (Smith, 1999). Block and Kelly (2001) elaborate on how the formal training provided to all new reference staff at their library has evolved into a voluntary, informal interactive professional development program. This ongoing training involves such activities as interactive group sessions, a compilation of reference competencies/basic skills needed at the reference desk, exchanges with other libraries, lectures and demonstrations of new electronic resources, and an in-house database of common reference questions and answers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This ongoing training involves such activities as interactive group sessions, a compilation of reference competencies/basic skills needed at the reference desk, exchanges with other libraries, lectures and demonstrations of new electronic resources, and an in‐house database of common reference questions and answers. They point to the need for these more informal training programs along with more formal ones to fill the constant need for updated professional knowledge (Block and Kelly, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When those components are present, outcomes are positive. A recent article by Block and Kelly (2001) discusses the program created at the University of Minnesota Bio-Medical Library to integrate informal staff development into reference work with a series of flexible, voluntary, and highly interactive components.…”
Section: Related Literaturementioning
confidence: 99%